METHODICAL TRAINING OF FUTURE PHYSICS TEACHERS ROLE OF ACT AND PROFESSIONAL DUTIES - Azamat Arslanboyevich Ismailov (Galaxy International Interdisciplinary Research Journal, 2022)
The priority task of training future teachers in HEIs is to form the teacher’s ability to solve professional problems. It is appropriate to use modern methods of teaching physics in general secondary schools. In order to strengthen students’ knowledge, it is necessary to adapt students to rapidly changing conditions, use information and communication technologies, and create virtualized knowledge.